Barbara Hepworth, the plasters the gift to Wakefield - Hepworth, Barbara 1903-1975.; Bowness, Sophie; Chipperfield, David; Guy, Frances; Heuman, Jackie; Jackson, Tessa; Wallis,Simon; Watson, Gordon; Wakefield Art Gallery and Museum (Farnham, Surrey Burlington, Vermont Lund Humphries Wakefield, West Yorkshire Hepworth Wakefield, 2011)
Celebrating the generous gift of Barbara Hepworth's plasters to The Hepworth Wakefield by the Hepworth Estate, this groundbreaking publication combines a fully illustrated catalogue of the sculptor's surviving prototypes in plaster, occasionally aluminium, with a detailed analysis of her working methods.
Coming home: Barbara Hepworth and the Wakefield Art Gallery collection / Frances Guy -- Developing the Hepworth Wakefield to start of construction, 1996-2007 / Gordon Watson -- The Hepworth Wakefield / David Chipperfield -- Barbara Hepworth's studio practice: plaster for bronze / Sophie Bowness -- Catalogue of the plasters and other prototypes in the Hepworth Gift / Sophie Bowness, with Jackie Heuman and Tessa Jackson -- The conservation of the gift / Jackie Heuman.
Keywords: Hepworth, Barbara -- 1903-1975.; Wakefield Art Gallery and Museum